2007
DOI: 10.1016/j.cell.2007.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Natively Unfolded Nucleoporins Gate Protein Diffusion across the Nuclear Pore Complex

Abstract: Nuclear pore complexes (NPCs) form aqueous conduits in the nuclear envelope and gate the diffusion of large proteins between the cytoplasm and nucleoplasm. NPC proteins (nucleoporins) that contain phenylalanine-glycine motifs in filamentous, natively unfolded domains (FG domains) line the diffusion conduit of the NPC, but their role in the size-selective barrier is unclear. We show that deletion of individual FG domains in yeast relaxes the NPC permeability barrier. At the molecular level, the FG domains of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
665
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 537 publications
(708 citation statements)
references
References 28 publications
41
665
2
Order By: Relevance
“…We observed interactions between Arx1 and Nup100, Nup116¤ and Nup57 ( Figure 7A). As a control we recapitulated the previously reported homotypic interaction of Nup116 FG domains ( Figure 7A) as well as interactions of Nup116 with other Nup FG domains (data not shown; Patel et al, 2007). These results support the previous biochemical identification of Arx1 nucleoporin association.…”
Section: Arx1 Physically Interacts With Nucleoporinssupporting
confidence: 78%
See 1 more Smart Citation
“…We observed interactions between Arx1 and Nup100, Nup116¤ and Nup57 ( Figure 7A). As a control we recapitulated the previously reported homotypic interaction of Nup116 FG domains ( Figure 7A) as well as interactions of Nup116 with other Nup FG domains (data not shown; Patel et al, 2007). These results support the previous biochemical identification of Arx1 nucleoporin association.…”
Section: Arx1 Physically Interacts With Nucleoporinssupporting
confidence: 78%
“…Thus, the ribosomal subunits might also employ multiple receptors. In addition, the channel of the NPC is comprised of disordered FG repeat-containing nucleoporins that form a mesh through weak hydrophobic interactions (Ribbeck and Gorlich, 2001;Denning et al, 2003;Patel et al, 2007). The highly electronegative ribosomal subunits likely require additional proteins to present hydrophobic surfaces that can partition into this milieu.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the two main FG repeat types (“FxFG/FG” and “GLFG”) are segregated in the NPC to define functionally distinct zones of the gating machinery 30 . In agreement, we find the FxFG/FG-type repeats to be enriched in the nuclear and cytoplasmic peripheries of the NPC, where the RNA-associating export platform and basket reside (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In opisthokonts, there are also only a few major FG repeat flavors, the majority of which fall into the category of either "GLFG"-like or "FxFG"-like. 44,45 We also know that there are 2 major kinds of transport factor: karyopherin-like, and nonkaryopherin-like, with very different preferences for FG repeat flavors. 46,47 Certainly, trypanosomes show us that FG flavor may not necessarily be all about nucleocytoplasmic positioning or imparting a directionality to nuclear transport.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%